Active Analysis as an Acting Method - Nazım Uğur Özüaydın (Konservatoryum)
Konstantin Stanislavski developed a brand-new working method in the last years of his life called active analysis that was different from the methods he had previously introduced. Active analysis is an acting method that does not appear in Stanislavski’s books, because he had passed away before finding the opportunity to write his findings and thoughts on the active analysis method. His student and assistant, Maria Knebel, was the one who had witnessed Stanislavski’s development of the active analysis method most closely, and she spread knowledge of this method in Russia with the articles and books she wrote on it in the 1950s. However, Knebel’s writings on active analysis would not be translated into English until 2016, thus leaving this method unknown outside of Russia until this time. This study aims to examine the active analysis technique in depth and evaluate its functionality as an acting method in light of the findings obtained from the detailed literature study as well as from practical studies with students from the acting departments of various universities. The study concludes the active analysis technique to reveal the creative potential of an actor, to allow actors to use all their abilities holistically and to create characters they can play completely organically.